Analysis The Implementation Of Program For Reducing Malnutrition Status Of Toddlers By Health Department Of Banda Aceh City - Maulya Ulfah (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
ABSTRACT, The National acceleration nutrition programe that has beenregulated by the goverment on govermental law number 42/2013, article Number2 Clause 1. Is an attempt beetwen goverment and the community throughparticipant and attention of the stake holders, planned and coordinated toaccelerate the refinement of nutrition, focus on 1000 days of first life.SevereMalnutrition status in the city of Banda Aceh in 2018 has increased compared tothe previous year. In 2008, there were 7 cases of severe malnutrition, 99 cases ofnutritional deficiencies, 194 stunting cases, and 575 cases of the baby BRL (belowred line) . This research is aimed to understand the implementation of program,the obstacles in the implementation of program as well as the effort made to dealwith the obstacles of the implementation of program on the reduction ofmalnutrition in toddlers by the health office of the city of Banda Aceh The methodused in this research is descriptive qualitative with data analysis techniques usingthe theory of policy implementation of George C. Edward III, includingcommunication, resources, disposition and bureaucratic structure. The results ofthis study are first, the implementation has been implemented however theimplementation is still not effective due to the lack of community’s participation in the Posyandu (integrated health post). Second, in the implementation process ofprogram of the Health office and Health Center, there are still communicationconstraints and human resources as well as inadequate facilities andinfrastructure. Third, the efforts to overcome obstacles in the implementation ofthe 1000 HPK program includes strengthening the posyandu (integrated healthpost), and strengthening the cooperation across programs and across sectors. Theconclusion of this study is that the regional government of the city of Banda Aceh,Health Office of the city of Banda Aceh and related parties are expected to increasecooperation with stakeholder for the successful implementation of the program onthe reduction of malnutrition in toddlers.Keywords: Implementation of Program, The Reduction of Malnutrition inToddlers, Health Office of the City of Banda Aceh.